SP7.4 Near-peer surgical simulation & teaching day for newly qualified FY1 doctors. (9th August 2022) - Thompson, Joe; Dodd, Eleanor; Morris, Rebecca; Wragg, Ashley; Gleeson, Joe
Abstract: Aims: The aims of this study were to ascertain how prepared newly qualified Foundation Year 1 (FY1) doctors felt for their surgical rotation and to evaluate the effectiveness of a surgical-themed teaching day for new FY1 doctors. Methods: A near-peer surgery-themed teaching day was delivered to 44 newly qualified FY1 doctors and delivered by clinical teaching fellows (FY3 doctors). The day involved four surgical-themed simulation scenarios: (i) haemodynamically unstable pancreatitis, (ii) anastomotic leak following ileocaecal resection, (iii) septic shower post ureteric stent and (iv) post-operative pulmonary embolism. Classroom-based teaching included: (i) microbiology and antibiotic prescribing (ii) interpreting abdominal films and (iii) insulin prescribing (including for nil by mouth patients). FY1s were randomly allocated a participant number and completed pre- and post-session anonymised questionnaires. Results: Only 31.7% (13/41) agreed that Medical School had adequately prepared them for their surgical foundation job and 46.3% (19/41) felt less prepared for surgical rotations compared with medical rotations. When compared with the pre-session scores: 93% (58% pre-session) felt prepared to manage acutely unwell surgical patients and 84% (43.9% pre-session) were confident with escalating patients to level 2/3 care. Confidence improved across the board for classroom-based sessions. Conclusion: This study has highlighted a need to ensure newly qualified FY1 doctors feel better prepared for their surgical rotations. The introduction of a mixed simulation and classroom teaching day has, in this instance, improved confidence across a number of important domains. Teaching delivered in the near-peer style may be the key to imparting relevant knowledge to new FY1s.